End-ligation can dramatically stabilize i-motifs at neutral pH. Issue 25 (8th March 2023) - El-Khoury, Roberto; Damha, Masad J.
Abstract : We report the significant stabilization of i-motifs at neutral pH due to end-ligation. The effect is even more pronounced when 2′-fluoroarabinocytidine substitutions are utilized in conjunction with end-ligation. Abstract : Stabilizing i-motif structures at neutral pH and physiological temperature remains a major challenge. Here, we demonstrate the use of chemical end-ligation to stabilize intramolecular i-motifs at both acidic and neutral pH. We also demonstrate that combining 2′-deoxy-2′-fluoroarabinocytidine substitutions and end-ligation results in an i-motif with an unparalleled thermal stability of 54 °C at neutral pH. Overall, the ligated i-motifs presented herein may be used in screens for selective i-motif ligands and proteins and could find important applications in nanotechnology.